2017
DOI: 10.1088/1741-4326/aa6456
|View full text |Cite
|
Sign up to set email alerts
|

Improving fast-ion confinement in high-performance discharges by suppressing Alfvén eigenmodes

Abstract: We show that the degradation of fast-ion confinement in steady-state DIII-D discharges is quantitatively consistent with predictions based on the effects of multiple unstable Alfvén eigenmodes on beam-ion transport. Simulation and experiment show that increasing the radius where the magnetic safety factor has its minimum is effective in minimizing beam-ion transport. This is favorable for achieving high performance steady-state operation in DIII-D and future reactors. A comparison between the experiments and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
(50 reference statements)
3
22
0
Order By: Relevance
“…Experiments and modeling have shown a variety of options for improving fast ion confinement in DIII-D q min [ 2 discharges. Modeling predicts, and some experimental evidence confirms, that further broadening of the q-profile can reduce AE-induced fast ion loss [63]. Specifically, increasing q 0 is predicted to eliminate Toroidal AEs by closing off the frequency gap in which they can exist, and increasing the radius of q min is predicted to lower the impact of Reverse Shear AEs on fast ion confinement by pushing the modes to a region of lower fast ion density.…”
Section: High Q Min Scenariomentioning
confidence: 89%
See 3 more Smart Citations
“…Experiments and modeling have shown a variety of options for improving fast ion confinement in DIII-D q min [ 2 discharges. Modeling predicts, and some experimental evidence confirms, that further broadening of the q-profile can reduce AE-induced fast ion loss [63]. Specifically, increasing q 0 is predicted to eliminate Toroidal AEs by closing off the frequency gap in which they can exist, and increasing the radius of q min is predicted to lower the impact of Reverse Shear AEs on fast ion confinement by pushing the modes to a region of lower fast ion density.…”
Section: High Q Min Scenariomentioning
confidence: 89%
“…Comparison of cases with high and low fast ion transport has suggested ways to improve the q min * 2 scenario [63] that the DIII-D EP program has begun to explore experimentally. For example, if the negative magnetic shear region can be expanded so that the q min radius is moved outwards where there are fewer fast-ions, then the drive of RSAEs (and perhaps other EP modes) should be greatly reduced, as shown in Fig.…”
Section: Potential For Control or Avoidance Of Aes To Improve At Scenmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, experiments and simulations in the literature 2,15,22,23 have shown that rapid long range frequency chirping across a wide range of frequency chirps (mode 'avalanching') is correlated with high amounts of fast ion loss. Other work has shown that mode-mode destabilisation may play a role in Alfvénic frequency chirping -activity in the KTF frequency range (∼ 1 kHz to 30 kHz) may instigate Alfvénic activity, and vice-versa.…”
Section: Fast Ion Lossmentioning
confidence: 99%